Small cleaning robot for office window - Ismayuzri, Ishak (2008)
Cleaning window for the office building is one of the important aspects in building maintenance activities which has been carried out regularly. The cleaning jobs are done by human might involve high risk. This project focuses on the development of a small cleaning robot for office window to substitute human force in window cleaning. The robot needs to satisfy certain criteria that are; portable, small size, lightweight,automatically operated and can clean all the corner of the windowpane. This robot is operated by suction cup with vacuum pump as the adhering mechanism and two wheels for the locomotion mechanism. The small amount of liquid is injected in between suction pad and glass surface to reduce the friction while operating. The body is made from acrylic to minimize weight of the robot. The robot is programmed using microcontroller and based on the window pane size. The application of the robot in the real world is hoped to help humans and reduce cost in office window cleaning activities.